Alternative Way for Organ Donation in Societies With Traditional Beliefs and Well Organized System of Emergency Medical Care. (August 2017) - Reznik, Oleg; Skvortsov, Andrey; Reznik, Aleksandr; Popova, Olga; Tishchenko, Pavel
Abstract : Substantial improvements in neurological and neurosurgical care in Russia in the last years led to imminent but expected decrease in organ donation rate. This trend inflicted the need to actively search for new ways to expand donor pool and resulted into emergence of two priority areas. First is based on the liberalization of brain death diagnostic criteria. Second one highlights the application of methods of artificial circulation. Brain death criteria liberalization will inevitably cause alterations in conventional relationship between doctor and patient. Adoption of artificial circulation approach induces the necessity to constructively rethink its role in saving person's life or, in case of failure, saving organs of deceased person for transplant. Resuscitation procedure algorithm, death record protocol for a patient with non-beating heart, but on artificial circulatory support as well as organ procurement procedure from such donor – all these represents complex non-medical, but socio-humanitarian, philosophical and theological issues. From 2009 till now our transplant team performed 35 procedures of extracorporeal membrane oxygenation in potential organ donors with 60 minutes after irreversible cardiac arrest followed by successful transplantation. Study design, perfusion protocols, procurement and transplant procedures were approved by the Scientific Board and the Ethics Committee of the Saint Petersburg State Research Institute for Emergency (Decision 7/0615/09) and authorized for clinical application by the Federal Advisory Service of the Ministry of Health of the Russian Federation (Resolution N2010/299). All donation and perfusion procedures were approved by local Ethics Committees and Institutional Review Board [1]. Our initial experience clearly demonstrates that new technical knowledge concerning artificial circulatory support in isolated human organs and organ systems all put together with integral knowledge about human (philosophical, theological, anthropological and medical) could lead to a breakthrough in the field of organ donation that does not violate the traditional views of society. Reference: 1. Reznik ON, Skvortsov AE, Reznik AO, Ananyev AN, Tutin AP, Kuzmin DO, et al. (2013) Uncontrolled Donors with Controlled Reperfusion after Sixty Minutes of Asystole: A Novel Reliable Resource for Kidney Transplantation. PLoS ONE 8(5): e64209.https://doi.org/10.1371/journal.pone.0064209 .